Evaluation of the Versius Robotic System for Infant Surgery-A Study in Piglets of Less than 10 kg Body Weight - Thomas Franz Krebs; Timo Kayser; Ulf Lorenzen; Matthias Grünewald; Marit Kayser; Anna Saltner; Lidya-Olgu Durmaz; Lina Johanna Reese; Ewan Brownlee; Katja Reischig; Jonas Baastrup; Andreas Meinzer; et al. (MDPI AG, 2023)
Background: We were able to demonstrate the feasibility of a new robotic system (Versius, CMR Surgical, Cambridge, UK) for procedures in small inanimate cavities. The aim of this consecutive study was to test the Versius® system for its feasibility, performance, and safety of robotic abdominal and thoracic surgery in piglets simulating infants with a body weight lower than 10 kg. Methods: A total of 24 procedures (from explorative laparoscopy to thoracoscopic esophageal repair) were performed in 4 piglets with a mean age of 12 days and a mean body weight of 6.4 (7-7.5) kg. Additional urological procedures were performed after euthanasia of the piglet. The Versius® robotic system was used with 5 mm wristed instruments and a 10 mm 3D 0° or 30° camera. The setup consisted of the master console and three to four separate arms. The performance of the procedure, the size, position, and the distance between the ports, the external and internal collisions, and complications of the procedures were recorded and analyzed. Results: We were able to perform all surgical procedures as planned. We encountered neither surgical nor robot-associated complications in the live model. Whereas all abdominal procedures could be performed successfully under general anesthesia, one piglet was euthanized early before the thoracic interventions, likely due to pulmonary inflammatory response. Technical limitations were based on the size of the camera (10 mm) being too large and the minimal insertion depth of the instruments for calibration of the fulcrum point. Conclusions: Robotic surgery on newborns and infants appears technically feasible with the Versius® system. Software adjustments for fulcrum point calibration need to be implemented by the manufacturer as a result of our study. To further evaluate the Versius® system, prospective trials are needed, comparing it to open and laparoscopic surgery as well as to other robotic systems.